2023
DOI: 10.1021/acsnano.2c10936
|View full text |Cite
|
Sign up to set email alerts
|

Light-Activated siRNA Endosomal Release (LASER) by Porphyrin Lipid Nanoparticles

Abstract: Lipid nanoparticles (LNPs) have achieved clinical success in delivering small interfering RNAs (siRNAs) for targeted gene therapy. However, endosomal escape of siRNA into the cytosol remains a fundamental challenge for LNPs. Herein, we report a strategy termed light-activated siRNA endosomal release (LASER) to address this challenge. We established a porphyrin-LNP by incorporating porphyrin-lipids into the clinically approved Onpattro formulation. The porphyrin-LNP maintained the physical properties of an LNP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 45 publications
(69 reference statements)
1
17
0
Order By: Relevance
“…In acidic environment, ionizable lipids (SM-102 and Cy-lipid in our system) are protonated to become positively charged, resulting in extra electrostatic repulsive force between these charged ionizable lipids and lead to the unstable structure, then the lipids may undergo rearrangement to fuse large sized assembly. [17] Most importantly, when the solution was irradiated by 1064 nm laser, spontaneous morphology change occurred and large sized aggregations were formed with particle size increased up to 4426.8 nm, which was consistent with TEM imaging findings (Figure 2h). These results clearly demonstrated that photothermally promoted NIR-II LNP morphology change is highly dependent on both acidic environment and NIR-II 1064 nm laser irradiation, which provided a prerequisite for remotely NIR-II light-triggered mRNA endosome escape.…”
Section: Methodssupporting
confidence: 87%
“…In acidic environment, ionizable lipids (SM-102 and Cy-lipid in our system) are protonated to become positively charged, resulting in extra electrostatic repulsive force between these charged ionizable lipids and lead to the unstable structure, then the lipids may undergo rearrangement to fuse large sized assembly. [17] Most importantly, when the solution was irradiated by 1064 nm laser, spontaneous morphology change occurred and large sized aggregations were formed with particle size increased up to 4426.8 nm, which was consistent with TEM imaging findings (Figure 2h). These results clearly demonstrated that photothermally promoted NIR-II LNP morphology change is highly dependent on both acidic environment and NIR-II 1064 nm laser irradiation, which provided a prerequisite for remotely NIR-II light-triggered mRNA endosome escape.…”
Section: Methodssupporting
confidence: 87%
“…The porphyrin lipids enabled LNPs to generate 1 O 2 upon light irradiation which disrupted the endosomal membrane, therby triggering siRNA endosomal escape to cytosol. 83 1.1.3. Biomaterial Modifications.…”
Section: Introductionmentioning
confidence: 99%
“…In the system, the therapeutic agents are conjugated/chemically linked with a light-sensitive photosensitizer. Upon exposure to light, the photosensitizers produce 1 O 2 which triggers the release of therapeutic agents at a site of interest and a desired time. For example, Mo et al developed singlet oxygen-responsive light-activated siRNA endosomal release (LASER) using porphyrin lipid nanoparticle (LNP) encapsulated siRNA to achieve an enhanced siRNA endosomal escape and significantly improved knockdown efficacy. The porphyrin lipids enabled LNPs to generate 1 O 2 upon light irradiation which disrupted the endosomal membrane, therby triggering siRNA endosomal escape to cytosol …”
Section: Introductionmentioning
confidence: 99%
“…There are two main patterns for extracellular particles to enter cells: membrane fusion and endocytosis. Most nanoparticles enter cells through endocytic pathways, including lipid nanoparticles, 17 solid lipid nanoparticles, 18 polymeric nanoparticles, 19 and most of inorganic nanoparticles. 12,20,21 Many nanoparticles, such as quantum dots (QDs), 22−24 gold nanoparticles, 25 and ultrastable organic dye nanoparticles, 26 are internalized into cells through clathrin-mediated endocytosis (CME).…”
mentioning
confidence: 99%
“…There are two main patterns for extracellular particles to enter cells: membrane fusion and endocytosis. Most nanoparticles enter cells through endocytic pathways, including lipid nanoparticles, solid lipid nanoparticles, polymeric nanoparticles, and most of inorganic nanoparticles. ,, Many nanoparticles, such as quantum dots (QDs), gold nanoparticles, and ultrastable organic dye nanoparticles, are internalized into cells through clathrin-mediated endocytosis (CME). For example, polystyrene nanoparticles can enter cervical epithelial (HeLa), lung epithelial (A549), brain astrocytoma, and macrophage (J774A.1) through the CME pathway. , Structurally, the size range of clathrin-coated vesicles is 60–120 nm, which is exactly suitable for most nanoparticles to be endocytosed.…”
mentioning
confidence: 99%